Anti-S. typhi Vi IgG levels in children with and without typhoid vaccinations - Sriandayani Sriandayani; Tonny H. Rampengan; Hesti Lestari; Novie Rampengan (Paediatrica Indonesiana, 2014)
Background Typhoid fever is endemic to Indonesia, with an annual incidence of 13/10,000 people. Vaccination has been shown to be an effective method to prevent typhoid fever. Of several vaccine types, the polysaccharide Vi vaccine is the most commonly used typhoid vaccine in developing countries. Results of previous studies remain inconclusive on the necessity of revaccination every 3 years.Objective To compare the mean serum anrioody titers of anti-S. typhi Vi IgG and the proportion of children with protective antibody levels between children with and without typhoid Vi vaccination.Methods We conducted a cross-secrional study at Tuminring District, 11anado from June to September 2012. Data was analyzed using independent T-test and Fisher's test. Serum anti-S. typhi Vi IgG levels were measured by enzyme-linked immunosorbent assay (ELISA) method.Results Seventy-six subjects were divided into two groups: 38 children who had received the typhoid Vi vaccination more than 3 years prior to this study and 38 children who never had typhoid vaccinations as a control group. No statistically significant difference in age and gender was found between the two groups. The mean serum anti-Vi IgG level was 0.55 ug/mL (SD 0.58; 95%CI 0.36 to 0.74) in the vaccinated group, significantly higher than that of the control group [0.31 ug/mL (SD 0.12); 950/Â£1 0.17 to 0.44; Pô€‚¥0.0381. The proportion of children with protective antiNi antioody level was higher in the vaccinated group (23.7%) than in the control group Â (10.5%), howevet; this difference was not statistically significant (P=0.128).Conclusion The mean serum anti-S. typhi Vi IgG antibody level in children who had been vaccinated more than 3 years prior to the study is higher than in children who had never received typhoid vaccinations. Nevertheless, the mean antibody titers are generally non-protective in ooth groups. Also, the proportion of children with protective antibody levels is not significantly different between the two groups.